Effect of protective solutions and hydroxyethyl starch in the attenuation of the injuries of ischemia and reperfusion of splanchnic organs - Ribeiro, Marcelo Eduardo [UNESP]; Sequeira, Julio [UNESP]; Trinca, Luzia Aparecida [UNESP]; Yoshida, Winston Bonetti [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2015)
PURPOSE: Vogt´s antioxidant solution (red blood cells, Ringer's solution, sodium bicarbonate, mannitol, allopurinol and 50% glucose) or its modification including hydroxyethyl starch (HES) were tested for the prevention of splanchnic artery occlusion shock. METHODS: Seventy rats were distributed in treatment (3), control (1), and sham (3) groups. Ischemia and reperfusion were induced by celiac, superior mesenteric and inferior mesenteric arteries occlusion for 40 min, followed by 60 min reperfusion or sham procedures. Controls received saline, both treatment and sham groups received the Vogt's solution, modified Vogt's solution (replacing Ringer's solution by HES), or HES. Mean arterial blood pressure (MABP), ileal malondialdehyde (MDA) and plasmatic MDA were determined, and a histologic grading system was used. RESULTS: At reperfusion, MABP dropped in all I/R groups. Only HES treatment was able to restore final MABP to the levels of sham groups. Plasmatic MDA did not show differences between groups. Ileum MDA was significantly higher in the control and treatment groups as compared to the sham group. Histology ranking was higher in the only in control group. CONCLUSIONS: Hydroxyethyl starch was able to prevent hemodynamic shock but not intestinal lesions. Both treatments with Vogt's solutions did not show any improvement.
Keywords: Ischemia; Reperfusion; Protective agents; Hydroxyethyl Starch Derivatives; Free radicals; Antioxidants; Rats